Teachers’ perspectives on factors of poor speaking skills among Arabic language students in Nigerian North central colleges of education - Muhammad, Usman (2021)
Previous literatures reveal that there is widespread of poor oral competence and communication skills among Arabic language students in Nigerian Colleges of Education. Factors such as inappropriate teaching method, unconducive learning environment and students' negative attitude towards language learning are identified as major challenges to learners' effective acquisition of the language. This phenomenon has been examined from learners’ perspectives without due consideration to teachers' perspectives. Hence, this research aimed at investigating factors that affect the speaking skills among Arabic students of Nigerian North Central colleges of education from teachers’ perspectives, and to identify statistically significant differences between the teachers views in each factor according to college and the teaching experience variables. Quantitative method was used in the research, and respondents consisted (36) Arabic language teachers from three colleges of education in North Central Nigeria who were purposefully selected based on their years of teaching experience and type of college. Considering the nature of the research questions, a questionnaire was used to collect the data that were analysed using a quantitative method of analysis. The research also adopted Krashen’s theory of second language acquisition for its interpretation. Both the descriptive and inferential statistics were used to analyse the results of the study. Means and Standard deviations were employed, and One-Way ANOVA test was conducted to find the differences in teachers' views on factors effecting students’ oral competence. Results revealed that the teachers' grades for the factors related to the learners’ attitudes got the highest marks with mean score of (4.361), followed by the learning environment with mean score of (4.322) and factors related to teaching methods came third with mean score of (4.098) while the factors related to teachers’ competence was ranked fourth with a mean score of (3.905), and the factors related to the syllabus recorded the least marks with mean score of (3.891). However, the result revealed that there were no statistically significant differences between the teachers' views on the factors based on the teaching experience and type of college which were greater than the significance level of (α = 0.05). Finally, the researcher recommended that learners' role and involvement in class activities should be taken to account in the teaching process, teachers should be encouraged to use interactive methods in teaching Arabic, a conducive educational environment that encourages the effective learning of Arabic communication should be provided and due consideration should be given to academic, educational and ethical standards while appointing teachers of Arabic in colleges of education learning of Arabic communication should be provided and due consideration should be given to academic, educational and ethical standards while appointing teachers of Arabic in colleges of education.